Impact of Universal Design for Learning (UDL) based Teaching Practices at Middle School Level on Students’ Creativity Skill - Ahmad, Sarmad; Shabbir, Muhammad; Rasool, Shafqat (Annals of Human and Social Sciences, 2025)
The objective of the study was to study the impact of teaching practices based on Universal Design for Learning (UDL) in regard to students’ creativity skill. Given the need to examine the effectiveness of teaching methodologies in enhancing the learning outcomes of students, the researcher studied the effectiveness of teaching based on the theory of UDL. This research utilized a quantitative research approach to explore the impact of teaching methods. The research compared two similar groups wherein the experimental group contained 21 students while the control group had 24 students. Results revealed that there was statistically significant difference in the mean score of creativity of the experimental group from pre-test to post-test. On the other hand, the mean score from pre-test to post-test of creativity skill of the control group were not significantly different. Thus, UDL principles should be made part of national curriculum to effectively accomplish national educational goals.